Elite vs. experienced male and female trail runners: comparing running economy, biomechanics, strength, and power - Besson, T.; Pastor, F. S.; Varesco, G.; Berthet, M.; Kennouche, D.; Dandrieux, P. E.; Rossi, J.; Millet, G. Y. (The Journal of Strength and Conditioning Research, 2023)
The increased participation in trail running (TR) races and the emergence of official international races have increased the performance level of the world best trail runners. The aim of this study was to compare cost of running (Cr) and biomechanical and neuromuscular characteristics of elite trail runners with their lower level counterparts. Twenty elite (10 females; ELITE) and 21 experienced (10 females; EXP) trail runners participated in the study. Cr and running biomechanics were measured at 10 and 14 km/h on flat and at 10 km/h with 10% uphill incline. Subjects also performed maximal isometric voluntary contractions of knee and hip extensors and knee flexors and maximal sprints on a cycle ergometer to assess the power-torque-velocity profile (PTVP). Athletes also reported their training volume during the previous year. Despite no differences in biomechanics, ELITE had a lower Cr than EXP (p < 0.05). Despite nonsignificant difference in maximal lower-limb power between groups, ELITE displayed a greater relative torque (p < 0.01) and lower maximal velocity (p < 0.01) in the PTVP. Females displayed shorter contact times (p < 0.01) compared with males, but no sex differences were observed in Cr (p > 0.05). No sex differences existed for the PTVP slope, whereas females exhibited lower relative torque (p < 0.01) and velocity capacities (p < 0.01) compared with males. Although not comprehensively assessing all determining factors of TR performance, those data evidenced level and sex specificities of trail runners in some factors of performance. Strength training can be suggested to lower level trail runners to improve Cr and thus TR performance.